Enhancing Teacher Competence: A Training Needs Analysis - Nur Fariha, Arini; Rahyasih, Yayah; Suharto, Nugraha; Dikdik, Asep (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study analyzes teacher training needs for developing pedagogical competencies at MTs Inovatif Daarul Ihsan through a quantitative method with a descriptive-exploratory approach. Data collected through the Training Needs Survey and analyzed using SPSS revealed that most teachers at the institution are classified as Level 2 (Decent) or Level 3 (Competent), with an average score of 34.31, below the established standard of 39. This finding indicates persistent professional inequality, particularly in pedagogical aspects, including lesson planning, subject matter expertise, teaching methods, and understanding of student characteristics. The predominantly young teaching staff further influences this competency gap. To address these needs, systematically designed training programs are required to cover pedagogical knowledge, innovative teaching models, and methodologies. The study recommends implementing comprehensive teacher pedagogical competency-based training focusing on three essential components: content knowledge, pedagogical knowledge, and pedagogical content knowledge. These competencies will enable teachers to not only master teaching methods but also apply them effectively to enhance student engagement and interaction in learning. This research provides valuable insights for policymakers, educators, and training institutions seeking to design more effective professional development programs to improve educational quality at MTs Inovatif Daarul Ihsan.